2021
DOI: 10.3390/ph14111071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gallic Acid-Coated Gold Nanoparticles as an Anti-Aging Ingredient

Abstract: Hyperglycemic environment-induced oxidative stress-mediated matrix metalloproteinase-1 (MMP-1) plays a crucial role in the degradation of the extracellular matrix (ECM), which might contribute to premature skin aging. Synthesized, environmentally friendly gallic acid-coated gold nanoparticles (GA–AuNPs) have been evaluated as an anti-aging antioxidant. Their microstructure was characterized by transmission electron microscopy (TEM), which showed that GA–AuNPs are spherical when prepared at pH 11. Dynamic light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Gold nanoparticles (GNPs) are excellent biological carriers because of their good biocompatibility. Moreover, gold is also reported to be an anti-aging metal [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (GNPs) are excellent biological carriers because of their good biocompatibility. Moreover, gold is also reported to be an anti-aging metal [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of synthesizing metal nanoparticles by reduction method, the reaction pH has a crucial influence on the synthesis success or failure of metal nanoparticles ( Wu, et al, 2021 ). To explore the effect of reaction pH on the number and morphology of AgNPs in GO-AgNPs, we synthesized GO-AgNPs at reaction pH of 3, 5, 7, 9, 11, and 13, respectively, and subjected them to Uv-vis characterization analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The cationic CTAB niosomes loaded with gallic acid demonstrated the highest anti-skin aging activity, including antioxidant (87.03 ± 0.99% cell viability) and inhibition of matrix metalloproteinase-2 (38.46 ± 1.53% of control) [20]. Another in vitro study on the inhibitory activity of gallic acid against MMP-1 in human nasopharyngeal carcinoma cells showed that gallic acid was able to inhibit the excessive production of ROS induced by UV light and was able to inhibit the activity of MMP-1 [21]. Other study examined gallic acid glucoside's potential as a cosmetic ingredient, including its antioxidant and anti-aging effects exerted by MMP-1 and collagen content.…”
Section: Discussionmentioning
confidence: 99%